2016
DOI: 10.1002/wnan.1444
|View full text |Cite
|
Sign up to set email alerts
|

Cerium oxide nanoparticles in neuroprotection and considerations for efficacy and safety

Abstract: Cerium oxide nanoparticles have widespread use in the materials industry, and have recently come into consideration for biomedical use due to their potent regenerative antioxidant properties. Given that the brain is one of the most highly oxidative organs in the body, it is subject to some of the greatest levels of oxidative stress, particularly in neurodegenerative disease. Therefore, cerium oxide nanoparticles are currently being investigated for efficacy in several neurodegenerative disorders and have shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 89 publications
3
65
0
Order By: Relevance
“…Among the biological effects of nanoceria, their neuroprotection capability is particular intriguing . For instance, Lee et al found that cerium oxide nanoparticles can induce changes in the murine neuronal cell transcriptome with a particular involvement of genes related to neurological disease, cell cycle control, and growth .…”
Section: Redox‐active Nanoparticlessupporting
confidence: 63%
See 1 more Smart Citation
“…Among the biological effects of nanoceria, their neuroprotection capability is particular intriguing . For instance, Lee et al found that cerium oxide nanoparticles can induce changes in the murine neuronal cell transcriptome with a particular involvement of genes related to neurological disease, cell cycle control, and growth .…”
Section: Redox‐active Nanoparticlessupporting
confidence: 63%
“…Nanoceria antioxidant and regenerating mechanism based on sequential SOD‐ and CAT‐like reactions. Adapted with permission …”
Section: Redox‐active Nanoparticlesmentioning
confidence: 99%
“…The degradation of the nanocomposite scaffold raises the question of the distribution of the CNPs throughout the body. Biodistribution studies completed in mice reported that CNPs do not cause an immunogenic response in the body (Hirst et al, ; Rajeshkumar & Naik, ; Rzigalinski, Carfagna, & Ehrich, ). Hirst et al () examined the accumulation of CNPs in the major organs of a rat: liver, spleen, lungs, kidney, heart, and brain.…”
Section: Discussionmentioning
confidence: 99%
“…3c), LR CNPs may have exerted their ROS scavenging effect by enhancing the cellular antioxidant enzyme activities as means of maintaining redox balance. CNPs are known for their broad spectrum antioxidant mechanisms 28,29 ; however, to the best our knowledge, the ability of CNPs to enhance cellular antioxidant enzyme activity in vitro has not been demonstrated. Due to limited studies in the field, the exact antioxidant mechanisms (scavenging of radicals, superoxides or peroxides) required for inhibiting valve calcification remain elusive.…”
Section: Resultsmentioning
confidence: 96%